2012
DOI: 10.1364/ol.37.003621
|View full text |Cite
|
Sign up to set email alerts
|

Emission polarization of random lasers in organic dye solutions

Abstract: This Letter presents a polarimetric study of the emission of random lasers from organic dyes. Coherent lasing modes from samples with ethanol solvent showed a high degree of polarization and did not influence each other in polarization. The proper choice of a laser dye with asymmetric absorption momenta, a highly viscous solvent, and a linear pump polarization can cause the random lasing emission to be completely linearly polarized for all wavelengths within the amplification range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…At the same year, Gottardo et al used extremely anisotropic scattering from small droplets of liquid crystals to create and manipulate polarized random laser emission [21]. In 2012, it was found that random lasers in organic dye solutions can be linearly polarized using the anisotropic adsorption of the dye molecules [22]. In [23], random laser emitted from DDNLCs was investigated, and any arbitrary linear polarization of RLs can be obtained by rotating the nematic liquid crystal sample.…”
Section: Introductionmentioning
confidence: 99%
“…At the same year, Gottardo et al used extremely anisotropic scattering from small droplets of liquid crystals to create and manipulate polarized random laser emission [21]. In 2012, it was found that random lasers in organic dye solutions can be linearly polarized using the anisotropic adsorption of the dye molecules [22]. In [23], random laser emitted from DDNLCs was investigated, and any arbitrary linear polarization of RLs can be obtained by rotating the nematic liquid crystal sample.…”
Section: Introductionmentioning
confidence: 99%
“…When the shear distance is 0 mm, the DOP is 0.1. The direction of dye's transition dipole moments is randomly distributed, thus only a small fraction of the overall emission could be polarimetrically evaluated [18].…”
Section: Resultsmentioning
confidence: 99%
“…As the liquid crystal droplets are gradually oriented in the shear direction, the scattering intensity is gradually reduced in perpendicular direction. The controllable intensity and polarization degree of random laser by shearing the DDPDLC have prospects of wide range of applications, such as optical sensors as a laser light source [29] and liquid crystal display [18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…That report was followed by a great number of papers from different authors that investigated on other physical systems for efficient RL operation. A large variety of materials has been tested in the past years, and recent publications on RLs describe, for example, experiments with dyes dissolved in transparent liquids, gels or liquid crystals with suspended micro or nanoparticles as light scatterers [12][13][14][15][16][17], powders of semiconductor quantum dots [18,19], dielectric nanocrystals doped with rare-earth ions [20,21], polymers and organic membranes doped by luminescent molecules [22][23][24][25][26][27], semiconductor and metallic nanowires structures [28][29][30][31], and even atomic vapors that present analogies with astrophysical lasers [32].…”
Section: Introductionmentioning
confidence: 99%